The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00432-004-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the MMP-1 promoter is correlated with histological differentiation of gastric cancer

Abstract: The presence of 2G allele in the MMP-1 promoter did not enhance the risk of gastric cancer; however, it may be involved in differentiation of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
6
33
1
1
Order By: Relevance
“…Similar gender differences in risk for the MMP-1 polymorphism were also found for renal cell and gastric cancer patients (16,17). Sex hormones including progesterone, estradiol, and ovarian steroids levels may decrease the MMP-1 expression levels and increase the tissue inhibitor levels of MMP-1 proteins (18)(19)(20).…”
Section: Discussionmentioning
confidence: 59%
“…Similar gender differences in risk for the MMP-1 polymorphism were also found for renal cell and gastric cancer patients (16,17). Sex hormones including progesterone, estradiol, and ovarian steroids levels may decrease the MMP-1 expression levels and increase the tissue inhibitor levels of MMP-1 proteins (18)(19)(20).…”
Section: Discussionmentioning
confidence: 59%
“…The SNPs of MMP1 (1607 1G/2G), MMP3 (1171 5A/6A), MMP7 (153 C/T), MMP8 (17 C/G) and MMP8 (799 C/T) are reported not to be associated with gastric cancer risk or prognosis [14,42,44,65] . AG genotype of the MMP13 77A/G polymorphism were reported to have a decreased risk of developing gastric cancer [39,41] .…”
Section: Gastric Cancermentioning
confidence: 99%
“…Recent epidemiological studies have demonstrated almost consistent results regarding the biological function of the MMP-1 promoter polymorphism and its association with the susceptibility or progression in several cancer types (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The 2G allele of the polymorphism has been reported to be related with increased risk of colorectal, lung, endometrial, ovary, kidney, and bladder cancers (4,(12)(13)(14)(15)(16)(17)(18)(19)(20), while the 2G allele was associated with tumor progression or patient survival but not with susceptibility of uterus, stomach, and colorectal (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%